Suppression of NLRP3 inflammasome by a small molecule targeting CK1α–β-catenin–NF-κB and CK1α–NRF2–mitochondrial OXPHOS pathways during mycobacterial infection - Guan, Qing; Xiong, Huan; Song, Xiangyu; Liu, Sheng; Guang, Yuanjun; Nie, Qi; Xie, Yan; Zhang, Xiao-Lian (Frontiers in Immunology, 2025)
IntroductionPyroptosis is an important inflammatory form of cell death and Mycobacterium tuberculosis (M.tb) chronic infection triggers excessive inflammatory pyroptosis of macrophages. Our previous research has confirmed that a small compound pyrvinium pamoate (PP) could inhibit inflammatory pathological changes and mycobacterial burden in M.tb-infected mice, but the potential mechanism of PP for inhibiting M.tb-induced inflammation remains unexplored.MethodsThe effects of PP on the NLRP3-ASC-Casp1 inflammasome assembly and activation, gasdermin D (GSDMD) mediated pyroptosis and inflammatory cytokines expression were assessed in human THP-1-derived macrophages after M.tb H37Rv/H37Ra/ Salmonella typhimurium (S. typhimurium) infection or LPS treatment by Transcriptome sequencing, RT-qPCR, Co-immunoprecipitation and Western Blot (WB) analysis. The lactate dehydrogenase (LDH) release assay was used to evaluate the CC50 of PP in M.tb-infected THP-1 cells.ResultsWe found that M.tb/S. typhimurium infection and LPS treatment significantly activate NLRP3-ASC-Casp1 inflammasome activation, GSDMD-mediated pyroptosis and inflammatory cytokines (IL-1β and IL-18) expression in macrophages, whereas PP could suppress these inflammatory effects in a dose dependent manner. Regarding the PP-inhibition mechanism, we further found that this inhibitory activity is mediated through the PP-targeting casein kinase 1A1 (CK1α)–β-catenin–NF-κB pathway and CK1α–NRF2–mitochondrial oxidative phosphorylation (OXPHOS) pathway. In addition, a CK1α specific inhibitor D4476 or CK1α siRNA could reverse these inhibitory effects of PP on bacteria-induced inflammatory responses in macrophages.ConclusionsThis study reveals a previously unreported mechanism that pyrvinium can inhibit NLRP3 inflammasome and GSDMD–IL-1β inflammatory pyroptosis via targeting suppressing CK1α–β-catenin–NF-κB and CK1α–NRF2–mitochondrial OXPHOS pathways, suggesting that pyrvinium pamoate holds great promise as a host directed therapy (HDT) drug for mycobacterial-induced excessive inflammatory response.